Technology, Media Literacy, and the Human Subject : A Posthuman Approach. - Lewis, Richard S. (Open Book Publishers, 2021)
What does it mean to be media literate in today's world? How are we transformed by the many media infrastructures around us? We are immersed in a world mediated by information and communication technologies (ICTs). From hardware like smartphones, smartwatches, and home assistants to software like Facebook, Instagram, Twitter, and Snapchat, our lives have become a complex, interconnected network of relations. Scholarship on media literacy has tended to focus on developing the skills to access, analyze, evaluate, and create media messages without considering or weighing the impact of the technological medium--how it enables and constrains both messages and media users. Additionally, there is often little attention paid to the broader context of interrelations which affect our engagement with media technologies.